Higher Negative Self-Reference Level in Patients With Personality Disorders and Suicide Attempt(s) History During Biological Treatment for Major Depressive Disorder: Clinical Implications - Bulteau, Samuel; Péré, Morgane; Blanchin, Myriam; Poulet, Emmanuel; Brunelin, Jérôme; Sauvaget, Anne; Sébille, Véronique (Frontiers in Psychology, 2021)
Objective: The aim of the study was to identify clinical variables associated with changes in specific domains of self-reported depression during treatment by antidepressant and/or repetitive Transcranial Magnetic Stimulation (rTMS) in patients with Major Depressive Disorder (MDD). Methods: Data from a trial involving 170 patients with MDD receiving either venlafaxine, rTMS or both were re-analyzed. Depressive symptoms were assessed each week during the 2 to 6 weeks of treatment with the 13-item Beck Depression Inventory (BDI13). Associations between depression changes on BDI13 domains (Negative Self-Reference, Sad Mood, and Performance Impairment), treatment arm, time, and clinical variables were tested in a mixed linear model. Results: A significant decrease of self-reported depressive symptoms was observed over time. The main characteristics associated with persistent higher depressive symptomatology on Negative Self-Reference domain of the BDI13 were personality disorders (+2.1 points), a past history of suicide attempt(s) (+1.7 points), age under 65 years old (+1.5 points), and female sex (+1.1 points). Conclusions: Early cognitive intervention targeting specifically negative self-referencing process could be considered during pharmacological or rTMS treatment for patients with personality disorders and past history of suicide attempt(s).